Prospective evaluation of contrast-enhanced ultrasound of breast BI-RADS 3-5 lesions - Janu, Eva; Krikavova, Lucie; Little, Jirina; Dvorak, Karel; Brancikova, Dagmar; Jandakova, Eva; Pavlik, Tomas; Kovalcikova, Petra; Kazda, Tomas; Valek, Vlastimil (BMC medical imaging, 2020)
BACKGROUND: To determine the benefit of contrast-enhanced ultrasound (CEUS) in the assessment of breast lesions. METHODS: A standardized contrast-enhanced ultrasound was performed in 230 breast lesions classified as BI-RADS category 3 to 5. All lesions were subjected to qualitative and quantitative analysis. MVI (MicroVascular Imaging) technique was used to derive qualitative analysis parameters; blood perfusion of the lesions was assessed (perfusion homogeneity, type of vascularization, enhancement degree). Quantitative analysis was conducted to estimate perfusion changes in the lesions within drawn regions of interest (ROI); parameters TTP (time to peak), PI (peak intensity), WIS (wash in slope), AUC (area under curve) were obtained from time intensity (TI) curves. Acquired data were statistically analyzed to assess the ability of each parameter to differentiate between malignant and benign lesions. The combination of parameters was also evaluated for the possibility of increasing the overall diagnostic accuracy. Biological nature of the lesions was verified by a pathologist. Benign lesions without histopathological verification (BI-RADS 3) were followed up for at least 24 months. RESULTS: Out of 230 lesions, 146 (64%) were benign, 67 (29%) were malignant, 17 (7%) lesions were eliminated. Malignant tumors showed statistically significantly lower TTP parameters (sensitivity 77.6%, specificity 52.7%) and higher WIS values (sensitivity 74.6%, specificity 66.4%) than benign tumors. Enhancement degree also proved to be statistically well discriminating as 55.2% of malignant lesions had a rich vascularity (sensitivity 89.6% and specificity 48.6%). The combination of quantitative analysis parameters (TTP, WIS) with enhancement degree did not result in higher accuracy in distinguishing between malignant and benign breast lesions. CONCLUSIONS: We have demonstrated that contrast-enhanced breast ultrasound has the potential to distinguish between malignant and benign lesions. In particular, this method could help to differentiate lesions BI-RADS category 3 and 4 and thus reduce the number of core-cut biopsies performed in benign lesions. Qualitative analysis, despite its subjective element, appeared to be more beneficial. A combination of quantitative and qualitative analysis did not increase the predictive capability of CEUS.
Keywords: dospělí; diferenciální diagnóza; nádory prsu; Female; Adult; mladý dospělý; ženské pohlaví; TI curve; lidé; Breast; Sensitivity and Specificity; Neoplasm Grading; prsy; Breast Neoplasms; Aged, 80 and over; senzitivita a specificita; Diagnosis, Differential; Ultrasonography, Mammary; Middle Aged; stupeň nádoru; prospektivní studie; Aged; kontrastní látky; Prospective Studies; Young Adult; Ultrasound; Contrast ultrasonography; ultrasonografie prsů; lidé středního věku; senioři nad 80 let; CEUS; senioři; Breast cancer; Contrast Media; Humans